Vaccination practices and preferences among muslim parents of young children : trends and misunderstandings - Mohamad Diah, Nurazzura; Samsudin, Suhaiza; Sedu, Nerawi (Contemporary Fiqh Research Unit IIUM & Islamic Book Trust, 2021)
Immunization has contributed to the improved health of millions of children worldwide. It has successfully reduced the burden of infectious disease for many decades. Prescribing children with enhances their quality of life. Despite its numerous benefits, the practice and preference for vaccination are still some of the main concerns in certain parts of the world, particularly in developing countries (Jheeta & Newell 2008).